THE EFFECT OF SERVICE QUALITY AND REPUTATION ON PATIENT LOYALTY AT POLY ORAL SURGERY - Fratiwi, Winda (Journal of Applied Health Management and Technology, 2024)
Background : Hospital is one of the health service facilities. Hospitals need to maintain the quality of their services, this health service is always required to always improve. The higher the quality of service will affect patient loyalty. The purpose of the research : to determine the effect of service quality and reputation on the loyalty of oral surgery poly patients at the Rumah Sakit Umum Daerah dr. Soekardjo Kota Tasikmalaya. Research method : the method used in this study is explanatory survey. How to test the effect of health care quality and reputation on patient loyalty with statistical tests path a nalyysis. The sample in this study was 63 oral surgery poly patients in Rumah Sakit Umum Daerah dr.Soekardjo Kota Tasikmalaya City. The results of the study :  the calculation of the value of the variable path coefficients (X 1), and (X2) against (Y), P YX1 is 0.439 and P YX2 is 0.417. Conclusion : quality of service and reputation affect thequality of oral surgery poly patients in Rumah Sakit Umum Daerah dr.Soekardjo Kota Tasikmalaya.